Situação de saúde de uma população atendida em um Centro de Saúde Escola de Uberlândia – Minas Gerais - Gabriel, Jôse Anne de França (2021)
Introduction: The Centro de Saúde Escola Jaraguá (CEJAR) in Uberlândia - MG is a primary care unit, with its organization and care strategy based on the traditional care model. The present research arised from one of the major problems experienced by CEJAR: the lack of knowledge of the territory and the health situation of the enrolled population, which makes difficult the strategic situational planning and Local Health Plan. Objective: To analyze the health situation of the population subscribed to CEJAR, to equip health professionals for the elaboration of a Local Health Plan that presents assistance, prevention and health promotion actions that can meet the needs and health problems of the enrolled population. Methods: The research was developed with a quantitative and qualitative approach, in four stages that allowed reaching the proposed objectives. First stage: a descriptive, cross-sectional study was carried out to evaluate the CEJAR, which included information regarding the structure of the unit, the work team and the Medical and Multiprofessional Residency programs. Second stage: a cross-sectional, quantitative, and descriptive study was carried out, with data related to the individual and family records of residents of the Jaraguá neighborhood attended at CEJAR, who are included in the e-SUS (data collected in 2018 and 2019). Third stage: maps were made by geoprocessing of the Jaraguá neighborhood, through micro-areas, which allowed the elaboration of a cartographic project, in which the database was defined, for descriptive analysis of the population's health problems. Fourth stage: focus groups were carried out with key representatives of the Jaraguá neighborhood, being a qualitative method that provides interaction between the participants and the researcher for the collection of data and the creation of new concepts and categories during the investigation. Result: It was observed that chronic diseases are prevalent and there are great difficulties in accessing specialized care. Final considerations: There is a need to insert some priorities into the Local Health Plan, to be developed annually. Keywords: Health situation; Local Health Plan; Access.